Food intelligence : the science of how food both nourishes and harms us - Belluz, Julia; Hall, Kevin, 1970- (Avery, an imprint of Penguin Random House, 2025)
"Nutrition isn't rocket science ; it's harder. There are new diet fads, bold claims about superfoods and articles promising the secrets to lasting weight-loss and longevity. The more 'expert' advice we hear about diet, the less clarity we have about what to eat. In Food Intelligence, award-winning health journalist, Julia Belluz, and internationally renowned nutrition and metabolism scientist, Kevin Hall, cut through the myths about nutrition to deliver a comprehensive book on food, diet, metabolism and healthy eating."--